SOCIAL ENTREPRENEURIAL VENTURES IN VIETNAM: AN IDEOGRAPHIC LENS - Yolanda Sarason; Kristi Yuthas; Linh Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Social entrepreneurial ventures are viewed as valuable tools for generating social and economic wealth and alleviating poverty in emerging economies. While there are many success stories of social ventures, there is a growing focus on the challenges in launching and managing social ventures in these economies. Social ventures in Vietnam face cultural obstacles and advantages that differ greatly from those in the US, where much of the research on social entrepreneurial ventures has focused. One key under-researched difference is culture. We use Hofstede’s cultural dimensions theory as an orienting framework for understanding cultural differences between the countries. We use this framework and three case studies of Vietnamese social ventures to develop a series of research propositions about the differences between Vietnam and the US. We suggest implications of these propositions for Vietnamese and US social entrepreneurs and managers and provide guidance for organizations seeking to form culturally sensitive partnerships. Trang’s vision for Fargreen’s business model was, “… to prove that businesses can do well by doing good, that you can build prosperous and sustainable farming communities, prioritize the environment and still create a successful enterprise. That’s why we called it Fargreen - going far by going green”... Trang contemplated how much easier it had been to develop Fargreen’s business model on paper than to implement it within the complex realities of Vietnam’s intricate social ties, evolving political and economic systems, difficult infrastructure, and unique history and culture. These factors amplified the challenges of balancing Fargreen’s financial objectives with its social mission (Sarason, Aziz, & Fifield, 2017).